"There's Something to Remind You that Everything Is Okay": Australian Trans Young People and the Presence of Animals in Interactions With Healthcare Professionals. (May 2023) - Riggs, Damien W.; Rosenberg, Shoshana; Fraser, Heather; Taylor, Nik
While animals have long been a focus in therapeutic spaces for young people via approaches such as animal-assisted therapies, there is a sense in which such approaches overlook the broader contribution that animals play by being present in young people's lives. In this article, we explore how the presence of animals (both physical and psychological) in interactions with healthcare professionals may hold specific meaning for trans young people living in Australia. Participants were recruited through Parents of Gender Diverse Children. Interviews were conducted in November 2021 with 17 trans young people and one of each of their parents living in Australia. All interviews were audio recorded, transcribed, and analyzed using thematic analysis. Two main themes were developed: (1) how healthcare professionals respond to conversations about animals and (2) the beneficial role of the presence of animals. The article concludes by discussing the importance of thinking about the presence of animals beyond existing frameworks and recognizing the value placed on the presence of animals by trans young people.